The Foundations Of The Creative Process And Manifestations Of Linguistic Formulation/ مرتكزات العملية الإبداعية وتجليات الصياغة اللغوية - Nisreen Awad Adham Zaher Al-Lahibi; Abdel Nasser Hashim Mohammed Al-Hiti (Ijaz Arabi Journal of Arabic Learning, 2026)
The grammatical meaning of displacement is one that stems not from the lexical connotation of a word, but rather from its syntactic context within the sentence, especially when this context is reconstructed in an unconventional manner. In this way, displacement is a factor that produces meaning, not merely a linguistic embellishment. The grammatical meaning of displacement represents a profound intersection between ancient rhetoric and modern linguistics, where language is understood not merely as a means of communication, but as an artistic tool for generating meaning through grammatical representation and deviation from it. In light of grammatical representation, displacement reveals the latent potential of language and opens an aesthetic horizon in which the eloquence of the slide from the ordinary to the surprising is manifested. Therefore, displacement, in the grammatical meaning, requires an active reader, not a mere passive recipient. The reader must reconstruct the relationships between vocabulary and decode the departure from the familiar to perceive the emotional or intellectual connotations underlying the text. Displacement, here, becomes a means of arousing astonishment and reinterpreting reality.